A Multimodal Analysis of English Courses’ Printed Advertisement at South Jakarta - Nia Liska Saputri (Peneliti.net, 2021)
This research entitled “A Multimodal Analysis of English Courses’ Printed Advertisement In South Jakarta” is a linguistic study of multimodal text which is concerned with texts that contain the interaction with both verbal and visual semiotic modes in order to achieve the communicative functions of the text. Multimodality or multimodal discourse analysis provides the tools and techniques to analyse texts which employ more than one mode of discourse. The objectives of this study are (1) to identify the verbal and visual elements of English Courses' brochures advertisement and (2) to describe the representation of verbal and visual elements of English Courses' brochures advertisement. This thesis is using qualitative descriptive to describe printed advertisement texts featuring verbal and visual elements consisted in the advertisements. In this thesis, the data that the writer analyzed is brochures as printed media of English Courses which located in South Jakarta. The instruments of collecting data in this thesis are observation, interview, and documentation. Halliday‟s Ideational Function and the Representational by Kress and van Leeuwen‟ are used to analyze the verbal and the visual texts. The results of the analysis is found that the most common verbal element used in the brochures is Announcement and the most common visual element used in the brochures is Lead. The verbal and visual elements are frequently represented by Material Process and Action Process.